Inflammatory Markers and Adipokines Alter Adipocyte-derived ASP Production Through Direct and Indirect Immune Interaction - Lu, H.; Gauvreau, D.; Tom, F.-Q.; Lapointe, M.; Luo, X. P.; Cianflone, K. (Experimental and Clinical Endocrinology & Diabetes, 2013)
Obesity and related metabolic diseases are associated with chronic low-grade inflammation, characterized by increased pro-inflammatory proteins. Several studies have demonstrated increases in acylation stimulating protein (ASP) and its precursor protein C3 in obesity, diabetes and dyslipidemia. To evaluate the effects of acute inflammatory factors and adipokines on ASP production and potential mechanisms of action, 3T3-L1 adipocytes were treated for 24 h with adipokines, cytokines, macrophage-conditioned media and direct co-culture with J774 macrophages. ASP and C3 in the media were evaluated in relation to changes in adipocyte lipid metabolism (cellular triglyceride stores). Leptin, adiponectin, IL-10, LPS and TNF-α increased ASP production (151%, 153%, 190%, 318%, 134%, P<0.05, respectively,). C5a and RANTES (Regulated and normal T cell expressed and secreted) decreased ASP production ( − 34%,  − 47%, P<0.05), which was also associated with a decrease in the precursor protein C3 ( − 39% to  − 51%, P<0.01), while keratinocyte chemoattractant (KC; murine IL-8 ortholog) had no effect on ASP and C3 secretion. By contrast, apelin, omentin and visfatin also decreased ASP ( − 27%,  − 49%,  − 22%, P<0.05), but without changes in precursor protein C3 secretion. Macrophage-conditioned media alone had little effect on C3 or ASP, while co-culture of adipocytes with macrophages markedly increased ASP and C3 production (272%, 167%, P<0.05). These in vitro results suggest various metabolic hormones and inflammatory factors can affect ASP production through increased precursor C3 production and/or by changing the rate of C3 conversion to ASP. As an adipokine, ASP could constitute a new link between adipocytes and macrophages.
Keywords: adipocytokines; inflammation; obesity